MUSIC AS A FORM OF RELIGIOUS EXPRESSION IN THE MEDIA: A SEMIOTIC AND REPRESENTATIONAL ANALYSIS OF THE SONG LYRICS TANPA AKU BY PANJI SAKTI.” - Siti Patimah; Fany Dwi Nanda; Ahmad Sarbini; Asep Iwan Setiawan (Indonesian Journal of Islamic Communication, 2025)
This study investigates the representation of religious values in Panji Sakti’s song “TanpaAku” as a contemporary manifesting of spiritual expression within popular media. Employing a qualitiative approach, the research utilizes Roland Barthes’ semiotic framework to analyze denotative and connotative meanings in the lyrics, and Stuart Hall’s theory of representation to examine how religious meanings are encoded by the creator and decoded by audiences. The analysis reveals that the song articulates core Islamic spiritual themes such as surrender to the Divine, the dissolution of ego, spiritual longing (mahabbah), and the human journey toward transcendence. These meanings are communicated through symbolic diction, metaphors, and acoustic aesthetics that enable a reflective, non-dogmatic mode of religious communication. Audience reception on digital platforms demonstrates predominantly dominant-hegemonic readings, indicating alighnment between the intended spiritual message and public interpretation. The findings affirm that popular music can function as an effective medium of contemporary dakwah, illustrating the mediatisation of religion whereby spiritual discourse is recontextualized through culture and digital forms. This study contributes to the understanding of how religious meaning is produced, represented, and internalized within the ecology of modern media.